2022
DOI: 10.3389/fnume.2022.953202
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical antibody-PET imaging of PD-L1

Abstract: Programmed cell death protein-1/ligand-1 (PD-1/PD-L1) blockade, including antibody therapeutics, has transformed cancer treatment. However, a major challenge in the field relates to selecting patients who are likely to respond to immune checkpoint inhibitors. Indeed, biopsy-based diagnostic tests to determine immune checkpoint protein levels do not accurately capture the inherent spatial and temporal heterogeneity of PD-L1 tumor expression. As a result, not all PD-L1-positive tumors respond to immunotherapies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, IHC is known to be a poor reflection of PD-L1 dynamic expression levels in both tumor and healthy tissue ( 31 ). Non-invasive detection of PD-1 or PD-L1 status using imaging techniques could be complementary to IHC and both preclinical and clinical trials have demonstrated its utility ( 32 34 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, IHC is known to be a poor reflection of PD-L1 dynamic expression levels in both tumor and healthy tissue ( 31 ). Non-invasive detection of PD-1 or PD-L1 status using imaging techniques could be complementary to IHC and both preclinical and clinical trials have demonstrated its utility ( 32 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive PET imaging using suitable tracers to track and assess the dynamic expression of PD-L1 and PD-1 has the potential to bring us one step closer to finding a more desirable response predictor, and could enable us to optimize those currently in use ( 36 ). Extensive preclinical and clinical research has been dedicated toward mAb-based PD-1/PD-L1 binders, and since there are already a number approved for clinical use, they were the obvious choice for initial development of PD-1/PD-L1-targeting imaging tracers ( 32 ). Notwithstanding the promising results from a number of PET imaging studies using mAbs, some intrinsic properties make them less suited as imaging tracers to assess the dynamics of PD-1/PD-L1 expression ( 38 42 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation